2019
DOI: 10.1055/s-0039-1700795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Obesity Influence in the Sexual Function of Postmenopausal Women: A Cross-Sectional Study

Abstract: Objective The incidence of obesity, which is a chronic condition, has increased in recent years. The association between obesity and female sexual dysfunction remains unclear, particularly in postmenopausal women. In the present study, we evaluated whether obesity is a risk factor for sexual dysfunction in postmenopausal women. Methods This is a cross-sectional study that analyzed data from interviews of postmenopausal women at the Climacteric Outpatient Clinic from 2015 to 2018. After applying the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…In our study, no significant difference was noted for female sexuality with BMI. Unlike ours, Dutra da Silva et al in their cross sectional study of 221 females of age 40–65 years found that compared to normal-weight women, obese and overweight postmenopausal women reported a higher index of sexual dysfunction in arousal and desire domains [21] .…”
Section: Discussioncontrasting
confidence: 76%
“…In our study, no significant difference was noted for female sexuality with BMI. Unlike ours, Dutra da Silva et al in their cross sectional study of 221 females of age 40–65 years found that compared to normal-weight women, obese and overweight postmenopausal women reported a higher index of sexual dysfunction in arousal and desire domains [21] .…”
Section: Discussioncontrasting
confidence: 76%
“…Regarding the studies presented in Table 1 , the highest reported prevalence of sexual dysfunction among obese women was 86% in a study conducted by Yaylali et al in 2010 in Turkey [ 18 ]. In overweight women, the highest prevalence was reported as 57.1% in a study conducted by Silva et al in 2019 in Brazil [ 21 ]. Conversely, the lowest prevalence of sexual dysfunction among obese women was reported as 12.8% in a study conducted by Erenel et al in 2013 in Turkey [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, obesity is also closely related to female sexual dysfunction. A cross-sectional study indicated that obesity was associated with an elevated likelihood of dysfunction in desire and arousal and reduced sexual satisfaction in postmenopausal females ( 31 ). Werlinger et al.…”
Section: Discussionmentioning
confidence: 99%